Wide-area collaboration in the aftermath of the March 11 disasters in Japan: Implications for responsible disaster management. (March 2015) - Aoki, Naomi
On 11 March 2011, an offshore earthquake of magnitude 9.0 and a massive tsunami hit the Tohoku region of Japan, followed by the Fukushima nuclear crisis. Despite these adversities, Tohoku is moving forward, and this extraordinary experience should guide us in the quest for responsible disaster management. A striking development after the disasters was the rise of wide-area collaboration, involving national and local governments, to help Tohoku municipalities. This study documents such collaboration in two areas – manpower support and debris processing. The empirical evidence suggests that the success of wide-area collaboration hinges on the success of both horizontal (interlocal) and vertical (inter-governmental) collaboration and that wide-area collaboration be added to future models predicting the effectiveness of recovery and reconstruction processes. Points for practitioners: It would be an error to assume that large-scale disasters will not occur in the future, and the challenge of wide-area collaboration faced by Japan this time naturally prompts the question of how to best design such collaborative governance in the country. This study offers a checklist of items policy makers need to specify when they design wide-area collaboration. The findings would seem to be most generalizable to disaster-prone unitary states with decentralized disaster management. The study sounds an alert that a decentralized system devoid of a plan for wide-area collaboration can be dangerous in times of crisis.